2015
DOI: 10.1615/critrevimmunol.2016015517
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Translation from the Bench: Therapeutic Intervention of the JAK/STAT Pathway in Neuroinflammatory Diseases

Abstract: Pathogenic CD4+ T cells and myeloid cells play critical roles in the pathogenesis of multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE), an animal model of MS. These immune cells secrete aberrantly high levels of pro-inflammatory cytokines that pathogenically bridge the innate and adaptive immune systems and damage neurons and oligodendrocytes. These cytokines include interleukin-2 (IL-2), IL-6, IL-12, IL-21, IL-23, granulocyte macrophage-colony stimulating factor (GM-CSF), and interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 179 publications
1
15
0
1
Order By: Relevance
“…In this study, we have investigated the IL-6/STAT3-, IL-12/STAT4-, and IL-23/STAT3-pathways in MS and the contribution of the genetic background to the responsiveness of these pathways. Earlier studies have indicated JAK/STAT-pathways as a potential therapeutic target in MS [21,22], and our finding of a donor-specific increased activity of the IL-12- and IL-23-induced STAT-pathways strengthens the perception that certain individuals may benefit from treatment. Previously, a phase II study tested the efficacy of a neutralizing antibody against the p40 subunit of IL-12 and IL-23 (ustekinumab), with the intention to block IL-12 and IL-23 signaling pathways in patients with RRMS.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we have investigated the IL-6/STAT3-, IL-12/STAT4-, and IL-23/STAT3-pathways in MS and the contribution of the genetic background to the responsiveness of these pathways. Earlier studies have indicated JAK/STAT-pathways as a potential therapeutic target in MS [21,22], and our finding of a donor-specific increased activity of the IL-12- and IL-23-induced STAT-pathways strengthens the perception that certain individuals may benefit from treatment. Previously, a phase II study tested the efficacy of a neutralizing antibody against the p40 subunit of IL-12 and IL-23 (ustekinumab), with the intention to block IL-12 and IL-23 signaling pathways in patients with RRMS.…”
Section: Discussionsupporting
confidence: 80%
“…Dysregulation of the JAK-STAT pathway resulted in autoimmune diseases, such as MS/EAE. Currently, many studies focus on the therapeutic targets of this pathway [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, STAT3 ablation worsens neuroinflammation in mice with spinal cord injury ( 56 ), and STAT3 activation alleviates cuprizone-induced CNS demyelination ( 57 ). This discordancy may depend on spatiotemporally specific activation of STAT3 ( 58 ). Indeed, in contrast to macrophages, IL-19 deficiency did not affect activation of DCs.…”
Section: Discussionmentioning
confidence: 99%